Influence of Biogenic Organics on the Chemical Composition of Arctic Aerosols. Issue 10 (15th October 2019) - Choi, J. H.; Jang, E.; Yoon, Y. J.; Park, J. Y.; Kim, T.‐W.; Becagli, S.; Caiazzo, L.; Cappelletti, D.; Krejci, R.; Eleftheriadis, K.; Park, K.‐T.; Jang, K. S.
Abstract: We use an ultrahigh‐resolution 15‐T Fourier transform ion cyclotron resonance mass spectrometer to elucidate the compositional changes in Arctic organic aerosols collected at Ny‐Ålesund, Svalbard, in May 2015. The Fourier transform ion cyclotron resonance mass spectrometer analysis of airborne organic matter provided information on the molecular compositions of aerosol particles collected during the Arctic spring period. The air mass transport history, combined with satellite‐derived geographical information and chlorophyll concentration data, revealed that the molecular compositions of organic aerosols drastically differed depending on the origin of the potential source region. The protein and lignin compound populations contributed more than 70% of the total intensity of assigned molecules when the air masses mainly passed over the ocean region. Interestingly, the intensity of microbe‐derived organics (protein and carbohydrate compounds) was positively correlated with the air mass exposure to phytoplankton biomass proxied as chlorophyll. Furthermore, the intensities of lignin and unsaturated hydrocarbon compounds, typically derived from terrestrial vegetation, increased with an increase in the advection time of the air mass over the ocean domain. These results suggest that the accumulation of dissolved biogenic organics in the Arctic Ocean possibly derived from both phytoplankton and terrestrial vegetation could significantly influence the chemical properties of Arctic organic aerosols during a productive spring period. The interpretation of molecular changes in organic aerosols using an ultrahigh‐resolution mass spectrometer could provide deep insight for understanding organic aerosols in the atmosphere over the Arctic and the relationship of organic aerosols with biogeochemical processes in terms of aerosol formation and environmental changes. Key Points: The molecular compositions of Arctic organic aerosols were identified using an ultrahigh‐resolution mass spectrometer (15T FT‐ICR MS) The molecular characteristics of Arctic organic aerosols showed distinct differences depending on their potential source origin The accumulation of biogenic organics in Arctic surface water could significantly influence the chemical properties of Arctic aerosols